PREVALENCE AND ASSOCIATED RISK FACTORS OF UNDER NUTRITION AMONG CHILDREN AGED 6 TO 59 MONTHS IN INTERNALLY DISPLACED PERSONS OF JALOZAI CAMP, DISTRICT NOWSHERA, KHYBER PAKHTUNKHWA - Ali, Waqar; Ayub, Ayaz; Hussain, Hamid (Journal of Ayub Medical College Abbottabad, 2015)
Background: The magnitude of under nutrition among children below five years of age is high in Pakistan. Undernutrition and infections are the two most important factors that affect the growth of children. This study explains the extent of undernutrition and prevalence of wasting and stunting among preschool children. Methods: This cross sectional study with a sample size of 446 covered the age group 6-59 months in Jalozai Camp, District Nowshera. Height for age, weight for age and weight for height were measured as per WHO guidelines. Systematic random sampling technique was used for sample selection. Data was collected using a questionnaire. Results: According to height for age Z-score, out of 446 children studied, 8.5% were stunted and 4.0% were severely stunted. According to weight for age Z score, 11.4% were underweight and 3.6% were severely underweight. According to weight for height Z-score, 4.0% were wasted and 2.7% were severely wasted. Conclusion: The undernutrition in children is comparable to the national figures. Although our study found that absence of formal education, big family size, late and early weaning, absence of exclusive breast feeding and poverty were the factors associated with undernutrition in children, they could cause increase in under nutrition in future if not improved.